Detection of Selection Signatures in Chinese Landrace and Yorkshire Pigs Based on Genotyping-by-Sequencing Data - Wang, Kai; Wu, Pingxian; Yang, Qiang; Chen, Dejuan; Zhou, Jie; Jiang, Anan; Ma, Jideng; Tang, Qianzi; Xiao, Weihang; Jiang, Yanzhi; Zhu, Li; Li, Xuewei; et al. (Frontiers in Genetics, 2018)
The domestic pigs have been undergone intense selection pressures for these development of intrested traits following domestication and modern breeding. This has altered many traits in most of pig breeds, such as growth rate, body weight, fertility and immunity. Thus, the objectives of this study were to (1) detect these selection signatures and identify the candidate genes that show evidences of recent artificial selection at the level of whole genome, (2) be beneficial to understand the relationship between genomic structure and phenotypic diversity, and (3) highlight the key roles of these candidate genes in growth and development in the two breeds. The data consisted of total raw number of 345570 single nucleotide polymorphisms (SNPs) in 1200 individuals from the Chinese Landrace pigs (L, n=600) and Yorkshire pigs (Y, n=600). Based on these SNPs data, two complementary methods, population differentiation (Fst) and composite likelihood ratio test (CLR), were carried out to detect the selection signatures in this study. A total of 540 potential selection regions (50kb) which contained 111 candidate genes were detected for Landrace-Yorkshire pair (L-Y) by Fst. In addition, 73 and 125 candidate genes were found for Landrace pigs and Yorkshire pigs by CLR test based on 321 and 628 potential selection regions, respectively. Some candidate genes are associated with important traits and signaling pathways including the ACACA, MECR, COL11A1, GHR, IGF1R, IGF2R, IFNG and MTOR gene. The ACACA and MECR gene are related to fatty acid biosynthesis. The COL11A1 gene is essential for the development of the normal differentiation. The GHR, IGF1R and IGF2R gene are significant candidate genes which play major roles in the growth and development in animals. The IFNG gene is associated with some aspects of immune response. The MTOR gene regulates many signaling pathways and signaling transduction pathway.